Solidifying agents and activated charcoal for in vitro culture of Solanum sessiliflorum - Rodrigues, Filipe Almendagna; Rezende, Renata Alves Lara Silva; Pasqual, Moacir; Lopes, Maria Teresa Gomes (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effects of the solidifying agents agar and phytagel and of activated charcoal on the in vitro cultivation of two maná cubiu (Solanum sessiliflorum) varieties: Thaís and Santa Luzia. The phytotechnical characteristics analyzed included number of leaves, number of roots, shoot and root length, and fresh matter of shoot and root. Regardless of the variety, phytagel was superior to agar as a culture medium. A greater number of leaves and longer shoots were observed in the Santa Luzia variety, in the absence of charcoal. The Thaís variety showed longer shoots and roots in the presence of charcoal.